1996
DOI: 10.1002/(sici)1097-4636(199604)30:4<463::aid-jbm4>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of size, concentration, surface area, and volume of polymethylmethacrylate particles on human macrophagesin vitro

Abstract: This study investigated effects of different sizes, concentrations, volumes, and surface areas of polymethylmethacrylate (PMMA) particles on human macrophages. Adherent peripheral blood monocytes isolated from five healthy individuals were exposed for 48 h to phagocytosable (0.325 micron and 5.5 microns) and nonphagocytosable (200 microns) spherical particles. Each particle size was tested over a range of concentrations (10(4)-10(11) particles per milliliter [0.325 micron], 10(2)-10(7) particles per milliliter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…It has been demonstrated that the cellular response to wear debris varies with the size, shape, composition, charge and concentration of particles (36,37). Furthermore, particle phagocytosis represents an important component of the cellular response to implants; thus, the size of wear particles may be a significant factor affecting osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the cellular response to wear debris varies with the size, shape, composition, charge and concentration of particles (36,37). Furthermore, particle phagocytosis represents an important component of the cellular response to implants; thus, the size of wear particles may be a significant factor affecting osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…As protein adsorption is known to vary based on material properties, three model polymers with distinct surface properties were investigated to determine whether the TLR2-dependent NF-κB/AP-1 activity observed on lysate-adsorbed surfaces was a robust effect . TCPS, PMMA, and PDMS were selected for their simple, nondegradable chemistry and widespread use in protein adsorption and macrophage activation literature, as the primary focus on the study was the cellular response to different adsorbed protein layers. Furthermore, PMMA and PDMS are clinically relevant biomaterials with well-characterized FBR. PMMA is a moderately hydrophobic polymer (WCA of 68–74°) , that is rigid and stiff at body temperature ( T g = 105 °C for spin-coated thin films) .…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar macrophages phagocytise spherical particles of 1-2 μm most effectively and uptake has been seen up to 5 μm [29]. In vitro, particles of 300 nm are less well phagocytised compared to 5 μm [30]. Particle uptake in macrophages for nano-sized TiO 2 has been estimated to be between 0.06 and 0.12% within 24 hours compared to micron sized particles.…”
Section: Discussionmentioning
confidence: 99%